(untitled) (Bulletin of the International Association for Paleodontology, 2021)
Description of morphological dental traits is an important concept within dental anthropology. The aim of this paper is to describe the case of occurrence of the enamel extensions in deciduous teeth in archaeological sample. The case of occurrence of enamel extensions on deciduous teeth from late medieval child’s skeletal remains is reported, along with other relevant data. Conclusion is that this might be the first such case described in medieval Bosnian archaeological population.